Padrões sinóticos associados a casos extremos de precipitação no Estado de São Paulo - Munhoz, Júlia Crepaldi (2022)
In this work, a study was made of the days in which precipitation events exceeded the 99% percentile in the state of São Paulo (SP), based on data from the automatic stations of the Instituto Nacional de Meteorologia (INMET), between the period from January to from 2010 to December 2019. The synoptic situations were analyzed through the pressure fields at mean sea level (PNMM), dynamic and thermodynamic fields for the day of the event. To obtain the PNMM standards on the day of the event, the Principal Component Analysis (PCA) methodology was used. The results show the circulation patterns associated with the occurrence of extreme precipitation events for the state of São Paulo, which represent approximately 74% of the cases selected in this study. The first dominant synoptic pattern shows a stationary frontal system over the state of São Paulo, the second pattern that encompasses several cases is a Convergence Zone, the third PNMM pattern is the result of a confluence of winds from a low east of the Andes and the counterclockwise circulation of the Subtropical South Atlantic High (ASAS) that carries moisture to the state of SP and the fourth pattern acquired is the result of moisture brought from the Amazon and a passing cold front.